Alexey Tolstoy and Alexey Remizov: Towards the History of Relations - Anna S. Uryupina (Studia Litterarum)
The article examines the history of the relationship between writers Alexei Remizov and Alexei Tolstoy based on archival materials from the collection of manuscript funds of the Vladimir Dal State Museum of the History of Russian Literature. These documents cover the period from 1908 to 1922. Among them are letters from Remizov addressed to Tolstoy; Tolstoy’s inscriptions in the guest albums of S.P. Remizova-Dovgello, Remizov’s wife; and some other records in the Remizov archive related to Tolstoy. The personal acquaintance of the writers took place between 1905 and 1907 after Remizov found himself with his wife in St. Petersburg after returning from exile. It is clear that the communication between the writers was largely friendly and was stopped only after 1922 in connection with Tolstoy’s return from emigration to Russia. Nevertheless, there is reason to believe that they may also have seen each other in 1935. Apparently, the Remizovs hosted Tolstoy when he came to Paris as part of the Soviet delegation to the International Congress of Writers in Defense of Culture in the summer of 1935.